(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study examines the comparative mental health profiles of athletes and non-athletes. Through a comprehensive review of existing literature and empirical evidence, it explores the psychological dimensions unique to each group. Key areas of focus include stress management, self-esteem, coping mechanism. By analyzing various factors such as lifestyle, social support, and the demands of their respective activities, the study aims to elucidate potential differences in mental health outcomes between athletes and non-athletes. Understanding these distinctions can inform targeted interventions and support systems to enhance the mental health of both groups, ultimately contributing to a more holistic approach to well-being across diverse populations.